Economics Of The Family, Gender, And Inequality - EN49 - 202302 - Cortes Fontcuberta Abucci, Manuel Pedro (2023)
This course will cover theoretical and empirical models of microeconomics of the family. The course will critically review the current literature on household economics (or economics of the family), with attention to assumptions made in modeling household decisions and issues with identifying empirical relationships and making causal inferences. We will discuss current applications of the economist¿s approach to studying the family. Relevant topics include marriage, divorce, investment in children, intergenerational transfers, and migration. To ensure that you receive a high quality and hopefully transformative educational experience, regular participation is a requirement of this class. Typical weeks include required reading, additional video or audio content, participating in discussion forums/projects, and leading class discussions. To be successful in this class, you will need to log in at least three times per week to access course materials and to participate actively in the class. I typically log in to D2L to monitor course activities every weekday, usually in the morning. Expect responses to questions posted in the class or sent by email within 48 hours, though I usually respond within 24 hours. I am not necessarily online on weekends due to other commitments. Please do your best to plan the timing of your questions accordingly. For class recordings, which are used at the discretion of the instructor, students must access content in D2L only. Students may not modify content or re-use content for any purpose other than personal educational reasons. All recordings are subject to government and university regulations. Therefore, students accessing unauthorized recordings or using them in a manner inconsistent with UArizona values and educational policies are subject to suspension or civil action. One of the main goals of this course is to conduct a critical reading of the current literature on the economics of the family. You are expected to do all the required reading and to participate in class discussions. Each of you is expected to present and lead the discussion on two sets of papers from the reading list (to be decided in the first class meeting). 1